Stereotactic radiotherapy as primary definitive or postoperative treatment of intracranial meningioma of WHO grade II and III leads to better disease control than stereotactic radiotherapy of recurrent meningioma - Lubgan, Dorota; Rutzner, Sandra; Lambrecht, Ulrike; Roessler, Karl; Buchfelder, Michael; Eyüpoglu, Ilker Yasin; Fietkau, Rainer; Semrau, Sabine (Journal of Neuro-Oncology, 2017)
The aim of this study was to evaluate long-term clinical outcome, prognostic factors and quality of life after adjuvant or definitive fractionated stereotactic radiotherapy (SRT) of meningioma WHO grade II and III or at recurrence. 131 patients with 138 meningioma (64 WHO grade II, 16 WHO grade III, 58 without histology) of the skull base, falx and convexity were treated between 01/2002 and 01/2015 at the Erlangen University Hospital by fractionated stereotactic radiotherapy (SRT) as primary treatment (adjuvant or definitive) and at recurrence. 53% (n = 53) lesions of patients with primary tumour received postoperative SRT and 47% (n = 47) as definitive treatment (without surgery). All 38 lesions (100%) of recurrent meningioma underwent surgery followed by SRT. SRT was mostly given in 28, 30 or 25 fractions to a median dose of 54.0 Gy in the reference point. Progression-free-survival at 8 years for patients with meningioma at primary treatment were significantly better with 100% for patients with definitive SRT (p = 0.008) or 85% for patients with adjuvant SRT (p = 0.009) compared to 42% after treatment (surgery + SRT) of recurrence. Progression-free-survival at 8 years for patients with SRT as adjuvant treatment after gross total resection of WHO grade II meningioma were significantly better at 83% (p = 0.016) compared to 46% after adjuvant SRT of recurrence. In 31% of patients after primary treatment and in 38.5% after recurrence treatment an improvement of pain symptoms was achieved. The favourable prognostic factor for better PFS at recurrence treatment was tumor location (skull base or convexity better compared to the falx). Postoperative SRT of WHO grade II meningioma after gross total resection (GTR) can effectively reduce recurrence risk.
EVALuna2:32870